PEMBELAJARAN DIFERENSIASI SEBAGAI PILAR IMPLEMENTASI KURIKULUM MERDEKA - Rosfiani, Okta; Saidah, Rafika Kauna; Itsnaini, Muhammad Fahmi; Rifaldi, Rafly Purnama; Firliansyah, Farhan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This qualitative study aims to examine the function of differentiated learning as the basis for implementing The autonomous curriculum in relation to accommodating the diversity of student needs. This research is motivated by the urgency of implementing The Self-Sustained Curriculum which emphasizes flexibility and independence in learning, where differentiation is a key strategy to realize the principle of